Use of Tomato (Lycopersicon-Esculentum) Seedlings to Detect Bensulfuron and Quinclorac Residues in Water - Gómez-De-Barreda, Diego; Lorenzo Rueda, Elena; Carbonell, Emilio A.; Cases, B.; Munoz, Niceto (2017)
During 1990, injury to tomatoes grown on the narrow land between the Albufera Lake (Spain) and the Mediterranean Sea was attributed to use of irrigation water coming from adjacent rice fields containing bensulfuron and quinclorac. A tomato root bioassay was developed to detect the herbicides in 10 ml of water. The assay was more sensitive to bensulfuron (0.5 ng ml-1) than quinclorac (100 ng ml-1). Only 30 ml of the affected water are necessary to conduct the test. Albufera water, sampled at three sites during 1991 and one during 1992 in the irrigation network canals caused different tomato main root length responses.